2016
DOI: 10.1177/0020715216637210
|View full text |Cite
|
Sign up to set email alerts
|

Homeland engagement and host-society integration: A comparative study of new Chinese immigrants in the United States and Singapore

Abstract: This paper addresses three main questions through a comparative study of new Chinese immigrants in the United States and Singapore: (1) How do contexts of emigration and reception affect the ways in which new immigrants are tied to their homeland? (2) How do diasporic communities develop to help members engage with the homeland? (3) What effects does transnationalism have on host-society integration? We develop an institutional approach to analyze how the state is involved in the transnational field and how di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…The migration and diaspora literature has portrayed the concept of ancestral home through investigations of the continuity of place attachment experienced by the first-or second-generation migrants (King & Christou, 2010;Maliepaard et al, 2010;Waite & Cook, 2011;Zhou & Liu, 2016). These studies argued that the quests for an ancestral home remained one of the most important issues in modern times.…”
Section: Diasporas and Their Ancestral Homementioning
confidence: 99%
“…The migration and diaspora literature has portrayed the concept of ancestral home through investigations of the continuity of place attachment experienced by the first-or second-generation migrants (King & Christou, 2010;Maliepaard et al, 2010;Waite & Cook, 2011;Zhou & Liu, 2016). These studies argued that the quests for an ancestral home remained one of the most important issues in modern times.…”
Section: Diasporas and Their Ancestral Homementioning
confidence: 99%
“…After independence, Singapore only took three decades to transform itself from a "third world" country to a fully industrialized and modernized country. In the late 1980s, the city-state encountered two daunting demographic challenges-the shortage of scientific and technological talents and the sharp decline of natural growth rate of the population, which threatened the country's competitiveness in economic globalization (Zhou and Liu 2016). Therefore, the government urgently adjusted its economic and immigration policies to attract high skilled immigrants.…”
Section: Contexts Of Receptionmentioning
confidence: 99%
“…While Singapore does not explicitly prefer any one ethnic group when it comes to attracting foreign talents and international students, it is believed that the government does prefer Chinese immigrants in order to replenish the potential decline of the ethnic Chinese population due to the extremely low fertility rate among Singaporean Chinese women (Tan 2003). One way was to directly recruit Chinese students who have received advanced degrees in Western countries, and the other was to offer generous scholarships to high school students in China to study in Singapore in the hope that those Chinese students would stay in Singapore after receiving college or advanced degrees at Singapore universities (Zhou and Liu 2016). Singapore's mainstream newspaper, The Straits Times, reported that the number of new Chinese immigrants rose from a couple of thousands in the early 1990s to more than one million in 2008.…”
Section: Contexts Of Receptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, these Chinese immigrant entrepreneurs, who are first‐generation immigrants emigrating from mainland China since 1980s, are referred to as new Chinese immigrant entrepreneurs (NCIEs) to distinguish them from other segments of ethnic Chinese entrepreneurs. This approach follows the tradition of mainstream research on Chinese immigrants (Chan & Koh, ; Gao, ; Ren & Liu, ; Zhou & Liu, ), although not all studies make this distinction (e.g., Batonda & Perry, ; Lund, Woods, Hibbins, & Barker, ).…”
Section: Introductionmentioning
confidence: 99%